A distinctive human fatty acid metabolism profile associated with osteoporotic patients - Xin Hu; Ruhai Lin; Jinyao Yan; Dan Wang; Yazhuo Liu; Deqiang Fu; Yinqiong Huang (Scientific Reports)
Abstract Evidence indicates a relationship between osteoporosis and nutritional factors. Nevertheless, the correlation between fatty acids and bone health remains not fully elucidated. This research sought to explore the potential associations between fatty acids (FAs) and osteoporosis. This study enrolled 248 patients in total. Basic demographic characteristics, serum phospholipid FAs, and bone mineral density were assessed. There were differences in arachidonic acid (AA) and docosapentaenoic acid (DPA) levels among the groups (P < 0.05). In the greatest quartile of docosahexaenoic acid (DHA) levels, the odds ratio (OR) in osteoporosis was 0.23 (0.05, 0.99); the corresponding value for AA was 0.2 (0.06, 0.64). In contrast, the risk of osteoporosis increased with elevated serum DPA; the highest quartile was associated with an OR of 13.44 for osteoporosis (4.82, 74.61). Receiver operating characteristic analysis showed that fatty acids have diagnostic value for osteoporosis (area under the curve 0.814; 0.751–0.867). Fatty acids are associated with bone mineral density. AA and DHA showed an inverse association with osteoporosis risk, while DPA was positively associated with osteoporosis risk.​ Therefore, the fatty acids metabolism profile might be a potential therapeutic target for osteoporosis.